2013
DOI: 10.1136/heartjnl-2012-303123
|View full text |Cite
|
Sign up to set email alerts
|

Trends in cardiovascular mortality and hospitalisations, and potential contribution of inhospital case-fatality rates to changes in national mortality in the Czech Republic 1994–2009

Abstract: During the study period, the overall CVD hospitalisation rates remained high but inhospital CFR declined considerably. The improved case-fatality seems to have made a substantial contribution to the decline in the national CVD mortality, particularly for AMI and stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 43 publications
(47 reference statements)
1
9
0
2
Order By: Relevance
“…22 Thus, the mortality trends we presented here are consistent with those reported for other European countries, although our study shows a more pronounced change of slope than other studies. Our study benefits from examining the longest follow-up period reported so far.…”
Section: Original Articlesupporting
confidence: 81%
“…22 Thus, the mortality trends we presented here are consistent with those reported for other European countries, although our study shows a more pronounced change of slope than other studies. Our study benefits from examining the longest follow-up period reported so far.…”
Section: Original Articlesupporting
confidence: 81%
“…Hospital admissions and deaths due to cardiovascular disease (CVD) complications and stroke reach a marked peak during winter months and drop in summer months, even in moderate climates (Davidkovova et al, 2013;Spencer et al, 1998). Several contributing factors can form a backdrop to these results, i.e.…”
Section: Introductionmentioning
confidence: 97%
“…This resulted in improved levels of hypertension control (men, 3% to 24%; women, 5% to 25%) [61]. These improvements in hypertension control could explain the observed reductions in CV death in the Czech Republic over time (from 561 per 100 000 [1994] to 357 per 100 000 [2009]) [62].…”
Section: Discussionmentioning
confidence: 99%